Chemical shift magnetic resonance imaging could predict subclinical cortisol production from an incidentally discovered adrenal mass. (6th April 2018) - Yener, Serkan; Secil, Mustafa; Demir, Omer; Ozgen Saydam, Basak; Yorukoglu, Kutsal
Summary: Context: To investigate whether any association between chemical shift magnetic resonance (MRI) findings, cortisol secretion and pathological findings exists that could predict subclinical hypercortisolism (SCH) in patients with adrenal incidentalomas (AI). Design: Retrospective, cross‐sectional study in a tertiary centre. Patients: Sixty‐eight subjects with AIs and 13 patients with Cushing's syndrome (CS). Patients with AIs were categorized according to cortisol levels post 1 mg dexamethasone (post‐DST). Measurements: Visual inspection of the lipid content of the adrenal tumour and calculation of adrenal‐to‐spleen ratio (ASR), the signal intensity index (SII), volume and the assessment of the association between pathological, radiological and hormonal findings in surgically treated patients. Results: Percentage of clear cells was correlated with ASR ( r = −.525, P = .01), SII ( r = .465, P = .025), post‐DST cortisol ( r = −.711, P < .001) and ACTH ( r = .475, P = .046). By ANOVA and post hoc analysis, patients with CS and five subjects with a post‐DST cortisol greater than 137 nmol/L differed significantly in ASR and SII from those with a post‐DST cortisol less than 50 nmol/L. An ASR level higher than 0.245 (OR 19.7, 95% CI 1.5‐257.5; P = .023) and a SII level lower than 78.37 (OR 15.6, 95% CI 1.2‐20; P = .034) remained as the independent predictors for SCH while age, presence of arterial hypertension or tumour volume did not make significant contribution to the models. Conclusions: Cortisol hypersecretion by adrenal adenomas is associated with distinctive MRI characteristics. The quantitative assessment of intracellular lipid in an AI could help distinguish patients with a clear phenotype of SCH.